Quimiometria associada à espectroscopia no infravermelho na previsão da eficiência de sequestrantes de H2S e supressores de poeira de minério de ferro - Moncioso, Natalia de Aquino Portela (2019)
The emission of particulate matter from the iron ore stockpiles is one of the concerns of the mining industry. In addition to the possible environmental and health damages, iron ore being the raw material for the steelmaking process is the economic problem. Sprinkling commercial water-soluble dust suppressants is a method of reducing or eliminating dust emission from ore stockpiles. Dust suppressants are aqueous solutions, sprayed on the surface of the ores, and there are several types available commercially. Already in crude oil exploration, the problems caused by the presence of H2S in oil production are diverse and comprehensive. In the petroleum industry several methods are used to remove this gas, with the use of commercial H2S scavengers being one of the most commonly used alternatives. There are a variety of commercial products known as H2S scavengers, which makes studies necessary to choose these products. In this thesis a methodology for evaluating the performance of commercial dust suppressors in iron ore storage stacks using the wind tunnel was studied. In addition, two performance prediction tests were proposed: for commercial H2S scavengers in oil and for commercial iron ore dust suppressants and using multivariate analysis of the infrared (IR) spectra in the middle region, considering that only one variable does not respond to the prediction of the performance of the samples, and associating bands in the IV evidenced in the graph of the loadings. The efficiency prediction test of H2S scavengers in capturing the sulfide in petroleum provided the estimation of the efficiency of the samples with 84% accuracy. It has been found that nitrogenous and extreme pH scavengers have a tendency to capture a greater amount of sulfide in the petroleum. In the test of prediction of the efficiency of the ore dust suppressors it was possible to discriminate samples with potential dust suppression with 86% accuracy. The high performance suppressors presented the hydrophobicity index of the IV bands at 2926/3300 cm-1 lower than 0.333.